Substructure imaging of heterogeneous nanomaterials with enhanced refractive index contrast by using a functionalized tip in photoinduced force microscopy. Issue 1 (December 2018) - Jahng, Junghoon; Yang, Heejae; Lee, Eun
ABSTRACT The opto-mechanical force response from light-illuminated nanoscale materials has been exploited in many tip-based imaging applications to characterize various heterogeneous nanostructures. Such a force can have two origins: thermal expansion and induced dipoles. The thermal expansion reflects the absorption of the material, which enables one to chemically characterize a material at the absorption resonance. The induced dipole interaction reflects the local refractive indices of the material underneath the tip, which is useful to characterize a material in the spectral region where no absorption resonance occurs, as in the infrared (IR)-inactive region. Unfortunately, the dipole force is relatively small, and the contrast is rarely discernible for most organic materials and biomaterials, which only show a small difference in refractive indices for their components. In this letter, we demonstrate that refractive index contrast can be greatly enhanced with the assistance of a functionalized tip. With the enhanced contrast, we can visualize the substructure of heterogeneous biomaterials, such as a polyacrylonitrile-nanocrystalline cellulose (PAN-NCC) nanofiber. From substructural visualization, we address the issue of the tensile strength of PAN-NCC fibers fabricated by several different mixing methods. Our understanding from the present study will open up a new opportunity to provide enhanced sensitivity for substructure mapping of nanobiomaterials, as well as local field mapping of photonic devices, such as surface polaritons on semiconductors, metals and van der Waals materials. Photoinduced force microscopy: Enhanced sensitivity Contamination of a scientific instrument is usually considered to be an undesirable outcome. However, researchers from Korea and Canada have now discovered that it can actually benefit an imaging technique called photoinduced force microscopy (PiFM). PiFM is a high-resolution scanning technique that is capable of mapping local refractive index contrast of a sample by measuring the light-induced force that arises between the sample and a closely-spaced tip. Junghoon Jang and coworkers from the Korea Research Institute of Standards and Science (KRISS) and the University of British Columbia have now discovered that the presence of a small amount of polydimethylsiloxane (PDMS) contaminant on the tip can serve to functionalize it and significantly increase the strength of the sample-tip interaction. The team has shown that the functionalized tip can map the substructure of nanofibres of a biomaterial called polyacrylonitrile-nanocrystalline cellulose.